(untitled) (Economics and region, 2020)
The article substantiates the role of the state in supporting participants of national and foreign exhibitions and fairs and processes of development of exhibition infrastructure. The international exhibitions and fairs are not only an important communication tool, but also a mechanism for promoting new technologies and products in national and international markets. A comparative description is made and the differences between fairs and exhibitions are determined. The structure of the distribution of exhibition areas in the world is analyzed and it is found that Europe has the largest number of exhibition complexes, the share of which is 46% of the global indicators. The dynamics of the main characteristics of exhibition activity in Ukraine from 2015 to 2019 is considered, which indicates the development of this area, but in 2018–2019 there was a certain decline in some indicators, including attendance at these events. The state of exhibition and fair activity in 2019 is analyzed in detail. The article identifies the prospects of exhibition and fair activities in Ukraine. Especially urgent is the solution of training, retraining and advanced training of employees of exhibition and fair activities, as well as the active participation of government agencies in the formation and development of international and national exhibitions and fairs.